Electrophysiological assessment of lower cranial nerve palsy triggered by spontaneous extracranial carotid dissection. Issue 1 (January 2019) - Salomone, G.; Ricci, S.; Rossi, F.; Turazzini, M.; Annese, V.; Del Colle, R.; Polo, A.
Abstract : A 43-year-old man was admitted to our department for the acute onset of unilateral right throbbing headache. Neurologic examination revealed right ocular myosis and ptosis, left displacement of the uvula, dysphonia, weak left-turning of the head, right scapular winging on arm abduction and right tongue deviation, suggesting 9th through 12th cranial nerve palsy and Horner's syndrome. Neurophysiologic examination confirmed the unilateral involvement. EMG showed loss of motor unit recruitment and denervation activity in the right sternocleidomastoid, trapezius and genioglossus muscles. MEPs and C-MAP were not excitable from those muscles. MRI demonstrated a crescent-shaped hyperintense T1 and T2 signal within the wall of the distal extracranial portion of the right internal carotid artery (ICA), suggesting an intramural hematoma causing mass effect upon the internal jugular vein. A diagnosis of spontaneous extracranial carotid dissection was made. An extended CT angiogram showed extensive luminal irregularities in the main renal arteries, with aneurysm formation at its bifurcation. Ibromuscular dysplasia was hypothesized and genetic counseling for connective tissue was carried on. Cranial nerve palsy is an unusual presentation of extracranial ICA dissection, likely mediated by compression or stretching of the nerve by the expanded artery. Neurophysiological testing provides useful information to localize the damage and to better understand the pathophysiology of the disease.